Drilling delamination study on carbon reinforced laminates - tool and feed rate effects - L. M. P. Durão (2011)
The characteristics of carbon fibre reinforced plastics had widespread their use. In order to join different components, drilling is often necessary. It is known that a drilling process that reduces the drill thrust force can decrease the risk of delamination. In this work, three combinations of the drilling process are compared: tool diameter and geometry and feed rate. The parameters considered for analysis include: thrust force, delamination extension and mechanical strength. This work shows that a proper combination of the drilling variables can contribute to reduce the delamination damage.